Assessment of Total Antioxidant Capacity in Serum of Heathy and Stressed Hens - Stefano Cecchini; Francesco Fazio (Animals, 2020)
Total antioxidant capacity (TAC) in healthy and dexamethasone-stressed hens was measured by applying four different spectrophotometric methods—the ferric reducing ability (FRAP) assay, the 2,2′-azino-bis (3-ethylbenzotiazoline-6-sulphonic acid) (ABTS) radical cation decolorization assay, the free radical scavenging activity (FRSA), and the total thiol levels (TTL). TAC assessed by all four methods did not change throughout the experimental period in the control group, whereas significant changes were shown by all adopted assays in the stressed group with some remarkable differences. TAC increased in the stressed group when FRAP and ABTS assays were applied, while it was reduced when sera were assessed by FRSA and TTL assays. Furthermore, FRAP assay was the only test able to show a significant change in TAC immediately after the end of the induced stress. At the end of the experimental period, TAC assessed by ABTS and FRSA assays showed a complete recovery in the stressed group, whereas TAC assessed by FRAP and TTL assays still showed significant persistent differences when compared to the control group. The observed differences in TAC are discussed in the light of the different contribution in each assay of the various antioxidant substances present in the samples.